75.3k views
2 votes
Solve: 9(y-2)-8y=-16

User Umi
by
5.9k points

2 Answers

5 votes

Answer:

y=2

Explanation:

9(y-2)-8y=-16

9y-18-8y=-16

9y-8y=-16+18

y=2

Hope this helps!

User Glenn Werner
by
5.7k points
2 votes
Let’s solve your equation step-by-step.
9( y- 2) - 8y =_16

Step 1: Simplify both sides of the equation

9(y-2)−8 y=−16

(9)(y)+(9)(−2)+−8y=−16

(Distribute)

9y+-18+-8y=-16

(9y+−8y)+(−18)=−16
(Combine like terms)

y + − 18 = − 16

y − 18 = − 16

Step 2: add to both sides

y − 18 + 18 = − 16 + 18

y=2

Answer: y=2
User Arthur Zangiev
by
5.4k points